Ten steps to nanette eaudiobook A memoir situation. - Gadsby, Hannah (Random House Audio, 2022)
NEW YORK TIMES BESTSELLER • Multi-award-winning Hannah Gadsby broke comedy with their show Nanette . In this “enthralling” ( The Washington Post ) memoir, they take us through the defining moments in their life and their powerful decision to tell the truth—no matter the cost. Don’t miss Hannah Gadsby’s Something Special, now streaming! “Hannah is a Promethean force, a revolutionary talent. This hilarious, touching, and sometimes tragic book is all about where their fires were lit.”—Emma Thompson A BEST BOOK OF THE YEAR: PopSugar, Vulture “There is nothing stronger than a broken woman who has rebuilt herself,” Hannah Gadsby declared in their show Nanette, a scorching critique of the way society conducts public debates about marginalized communities.    Gadsby grew up as the youngest of five children in Tasmania, where homosexuality was illegal until 1997. After moving to mainland Australia and receiving a degree in art history, they found themselves adrift, working itinerant jobs and enduring years of isolation punctuated by homophobic and sexual violence. When Gadsby was twenty-seven, a friend encouraged them to enter a stand-up competition. They won, and so began their career in comedy.   Gadsby became well known for their self-disparaging humor, but in 2015, as Australia debated the legality of same-sex marriage, they started to question this mode of storytelling, beginning to work on a show that would transform their career and would become “the most-talked-about, written-about, shared-about comedy act in years” ( The New York Times ).  Harrowing and hilarious, Ten Steps to Nanette traces Gadsby’s growth as a queer person, their ever-evolving relationship with comedy, and their struggle with late-in-life diagnoses of autism and ADHD, finally arriving at the backbone of Nanette: the renouncement of self-deprecation, the rejection of misogyny, and the moral significance of truth-telling.